The productivity and income effects of adoption of improved soybean varieties and agronomic practices in Malawi - Hirpa Tufa, A.; Alene, A.; Manda, J.; Akinwale, M.G.; Chikoye, David; Feleke, S.; Assfaw Wossen, Tesfamicheal (Elsevier, 2019)
Soybean constitutes an important component of the maize-based smallholder cropping systems in Malawi and holds considerable potential for countering soil fertility decline, enhancing household food and nutrition security, and raising rural incomes. A number of yield-enhancing improved soybean varieties and agronomic practices (ISVAPs) have been developed and disseminated in Malawi, but there is limited evidence on the adoption and impacts of these technologies. This paper assesses the productivity and income effects of adopting ISVAPs using plot level data collected from a nationally representative sample of 1237 soybean growing households in Malawi. Our results show that over a third of the sampled households have adopted ISVAPs. Furthermore, results from a stochastic dominance analysis showed that soybean yields and net crop incomes for adopters are significantly higher than those of non-adopters over the entire probability distribution of ISVAPs adoption. Endogenous switching regression model results further demonstrated that adoption of ISVAPs is associated with an average of 61% yield gain and 53% income gain for adopters. Overall, the results point to the need for further scaling of ISVAPs for greater adoption and impact on the livelihoods of smallholder farmers in Malawi.